Feeding strategies of four dominant copepod species in Prydz Bay, Antarctica: Insights from a combined fatty acid biomarker and stable isotopic approach. (August 2016) - Yang, Guang; Li, Chaolun; Guilini, Katja; Peng, Quancai; Wang, Yanqing; Zhang, Ye; Zhang, Yongshan
Abstract: Using fatty acid biomarkers and stable isotopic signatures, we investigated the feeding strategies and dietary preferences of four dominant copepod species ( Calanoides acutus, Calanus propinquus, Metridia gerlachei and Rhincalanus gigas ) sampled during the late austral summer in Prydz Bay, Antarctica. Our results show that diatoms, dinoflagellates and ciliates dominated copepod food sources (hypothesized to be phytoplankton and particulate organic matter) in the inner bay regions more than in the oceanic regions of Prydz Bay. Regional differences in the composition and abundance of food sources were also reflected in the fatty acid biomarkers and stable isotopic values. In the inner bay region, the total fatty acid contents of these food sources were nearly twofold higher, including greater contributions from fatty acids of dinoflagellate origin; these samples also had higher δ 13 C and δ 15 N values. Fatty acid biomarkers and stable isotopic values in copepod species roughly mirrored the spatial patterns in food sources. As found in the primary producers, the concentrations of dinoflagellate fatty acids and δ 13 C and δ 15 N values were higher in copepods from the inner bay regions. Additionally, there were inter-species differences in the fatty acids and stable isotopic values of copepods. C. acutus and C. propinquus did not exhibit significant regional differences in their total fatty acid contents. In contrast, M. gerlachei from the inner bay region had higher fatty acid values. C. acutus and C. propinquus had higher compositions of the long chain fatty acids 20:1n-9, 22:1n-9 and 22:1n-1, while docosahexaenoic acid (DHA) was higher in M. gerlachei. The δ 15 N values indicate that C. acutus occupies a higher trophic level than the other copepod species. Similarly, higher fatty acid ratios in M. gerlachei, including DHA/EPA(eicosapntemacnioc acid) and 18:1n-9/18:1n-7, indicate that this species feeds more opportunistically and prefers a carnivorous diet. Insights from this combined fatty acid and stable isotopic approach suggest that the dominant copepod species in Prydz Bay, Antarctica, have flexible feeding strategies that vary by food source during the late austral summer. Highlights: Regional differences in composition and function of food sources in Prydz Bay. Species-specific and regional differences in copepods feeding strategies. Calanoides acutus would prefer omnivorous diet during late austral summer. A high trophic plasticity of the dominant copepods in the Prydz Bay ecosystem.